Perceived Leader Behavior as a Function of Personality Characteristics of Supervisors and Subordinates - Durand, Douglas E.; Nord, Walter R. (Academy of Management Journal, 1976)
Subordinate perceptions of supervisory initiation of structure and consideration were studied as a function of locus of control and Machiavellianism. Personality was found to be a major factor in predicting leader behavior as perceived by subordinates. Locus of control may be an important personality dimension influencing the leadership process in organizations.